2007
DOI: 10.1089/dna.2006.0564
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression and Localization of the Epinecidin-1 Antimicrobial Peptide in the Grouper (Epinephelus coioides), and Its Role in Protecting Fish Against Pathogenic Infection

Abstract: Epinecidin-1 is an antimicrobial peptide and plays a vital role in protecting fish against pathogenic infection. As a mimic of a grouper epinecidin-1 peptide, it has tertiary structures that closely resemble those of pleurocidin found in the winter flounder (Pleuronectes americanus). The tissue-specific, lipopolysaccharide (LPS)-stimulation-specific, and poly(I):poly(C)-stimulation-specific expressions of the grouper (Epinephelus coioides) epinecidin-1 antimicrobial peptide were determined using a comparative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
84
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(89 citation statements)
references
References 33 publications
5
84
0
Order By: Relevance
“…V. anguillarum is known to enter its fish host through the portals of the skin, the gut, and the gills and has been shown to move by chemotaxis toward mucus secretions from multiple epithelial tissues, including the skin and the intestine (27). Fish epithelial tissues secrete innate immune effectors, including AMPs (10,28). The increase in the cumulative mortality of medaka following challenge with V. anguillarum that was previously exposed to cecropin B suggests that successful colonization of the fish by V. anguillarum depends on its ability to resist the actions of AMPs.…”
Section: Discussionmentioning
confidence: 99%
“…V. anguillarum is known to enter its fish host through the portals of the skin, the gut, and the gills and has been shown to move by chemotaxis toward mucus secretions from multiple epithelial tissues, including the skin and the intestine (27). Fish epithelial tissues secrete innate immune effectors, including AMPs (10,28). The increase in the cumulative mortality of medaka following challenge with V. anguillarum that was previously exposed to cecropin B suggests that successful colonization of the fish by V. anguillarum depends on its ability to resist the actions of AMPs.…”
Section: Discussionmentioning
confidence: 99%
“…The blood samples were centrifuged, and sera were collected. The concentration of epinecidin-1 in sera was determined by liquid chromatography-mass spectrometry/mass spectrometry (LC-MS/MS), following a previously published protocol and procedure (23).…”
Section: Bacteria and Cellsmentioning
confidence: 99%
“…The central role of AMPs in host defense makes them potential candidates for the treatment of infections (21)(22)(23), and the effects of several AMPs on P. aeruginosa infection have been analyzed in vitro (21). Recently, we identified a cDNA sequence from Epinephelus coioides that encodes a peptide named epinecidin-1; we found that epinecidin-1 is active against Gram-negative and -positive bacteria, viruses, Candida albicans, and Trichomonas vaginalis in vitro and in vivo (23)(24)(25)(26).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A large number of AMPs have been isolated from a wide number of fish species during last years, among which pleurocidin from winter flounder (Pleuronectes americanus) [2], cathelicidins from rainbow trout (Oncorhynchus mykiss) [3], defensins from zebrafish (Danio rerio) [4], piscidins from hybrid striped bass (white bass, Morone chrysops, female, x striped bass, Morone saxatilis, male) [5], dicentracin from sea bass (Dicentrarchus labrax) [6], and hepcidin from channel catfish (Ictalurus punctatus) [7], epinecidin from the grouper (Epinephelus coiodes) [8] (for a review see [9]). The activity of fish AMPs have been tested not only against the more common fish bacterial pathogens [8,10] but either against other pathogens like nervous necrosis virus [11]. Moreover, some AMPs have shown dual functional aspects, like hepcidins that have been indicated to be involved in iron regulation [12].…”
Section: Open Accessmentioning
confidence: 99%